Can rural cooperatives reduce poverty vulnerability of smallholder households? Evidence from rural Western China - Liu, Jianzhong; Yang, Mingwei; Zhang, Zhiyong (Frontiers in Sustainable Food Systems, 2023)
Introduction Poverty eradication is one of the global challenges, and rural cooperatives provide an effective path to address smallholder households’ poverty. However, the effect of poverty reduction can show heterogeneity depending on the economic capital, human capital, and social capital of households. Methods Based on comprehensive research data on the poverty status of 1,622 smallholder households in four provinces in the less developed regions of western China, using OLS and PSM models, this paper empirically analyzes the impact and heterogeneous characteristics of rural cooperatives on the poverty vulnerability of smallholder households. Results/Discussion The results show that rural cooperatives have a significant dampening effect on the poverty vulnerability of smallholder farmers, and the findings hold true after robustness tests using multiple methods. The impact of rural cooperatives on the poverty vulnerability of farming households differed significantly across smallholder households with different characteristics. Specifically, participation in cooperatives had a more pronounced effect on reducing poverty vulnerability among non-poor, higher human capital and higher income farm households compared to poor, lower human capital and lower income farm households. The results of the study can provide a useful reference for policy-making on rural mutual assistance and poverty reduction among farmers.